Предмет: Алгебра, автор: DenisKuber

Помогите решить!!!!!!!!!!!!!!!

Приложения:

Ответы

Автор ответа: Аноним
0
1
(x+4)(y-1)-(x+4)(x+1)=0
(x+4)(y-1-x-1)=0
1)x+4=0
x=-4
подставим во 2
16-y²+12+8=0
y²=36
y1=-6
y2=6
(-4;-6);(-4;6)
2)y=x+2
подставим во 2
x²-x²-4x-4-3x+8=0
-7x=-4
x=4/7
y=2 2/7
(4/7;2 4/7)
Ответ (-4;-6);(-4;6);(4/7;2 4/7)
2
[1/(3x-1)(3x+2)+1/(3x+2)(3x+5)]+[1/3x+5)(3x+8)+1/(3x+8)(3x+11)]=
[(3x+5+3x-1)/(3x-1)(3x+2)(3x+5)]+[(3x+11+3x+5)/(3x+5)(3x+8)(3x+11)]=
=(6x+4)/(3x-1)(3x+2)(3x+5)+(6x+16)/(3x+5)(3x+8)(3x+11)=
=2(3x+2)/(3x-1)(3x+2)(3x+5)+2(3x+8)/(3x+5)(3x+8)(3x+11)=
=2/(3x-1)(3x+5)+2/(3x+5)(3x+11)=(6x+22+6x-2)/(3x-1)(3x+5)(3x+11)=
=(12x+20)/(3x-1)(3x+5)(3x+11)=4(3x+5)/(3x-1)(3x+5)(3x+11)=
=4/(3x-1)(3x+11)
x=(√3-5)/3
4/(√3-5-1)(√3-5+11)=4/(√3-6)(√3+6)=4/(3-36)=-4/33


Похожие вопросы
Предмет: Русский язык, автор: darivhanmadiar